Peran Kepemimpinan dalam Meningkatkan Budaya Keselamatan Pasien di Rumah Sakit (Suatu Kajian Kepustakaan) - Nikita Nabilla; Dhamanti, Inge (LPPM Hang Tuah Pekanbaru, 2023)
One of the elements that contribute to patient safety issues is poor leadership. Leadership is an essential component of changing the culture of patient safety. This literature review aims to examine the role of leadership in enhancing hospital patient safety culture. The method employed is a review of the literature using articles published between 2017 and 2022. The literature was gathered using the terms